PENGEMBANGAN E-MODUL BERBASIS LIVE WORKSHEET MATERI MENULIS PUISI SISWA KELAS IV SEKOLAH DASAR - Wati, Siti Fajar; Denna Delawanti Chrisyarani; Dwi Agus Setiawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In learning Indonesian in elementary schools, teachers only use traditional and conventional teaching materials such as the use of PPT (power point). So that students easily get bored in the learning process in class. The purpose of this study was to determine the validity, practicality, and effectiveness of the development of E-Modules based on Live Worksheets for writing poetry for grade 4 elementary school students. This development research uses the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data analysis in this study used qualitative and quantitative. Based on the results of the assessment of media experts, the percentage was 93.75%, material experts 95.45%, language experts 100%, from the three experts they got an average of 96.4% with the category "very valid". The results of the teacher's practicality test obtained 93.75% with the category "very practical", while limited trials by students obtained 88.05% with the category "very practical", and extensive trials obtained 90.17% with the category "very practical". Meanwhile, the effectiveness test using the N-Gain score obtained 0.7 with the category "moderate" and in percent obtained 66.5 with the category "Effective". So it can be concluded that the use of E-Module based on Live Worksheet is valid, practical, and effective to be used as a medium for learning Indonesian in Elementary Schools.